2020
DOI: 10.1007/s10143-020-01393-1
|View full text |Cite
|
Sign up to set email alerts
|

Limits and pitfalls of indirect revascularization in moyamoya disease and syndrome

Abstract: Moyamoya vasculopathy is a rare chronic cerebrovascular disorder characterized by the stenosis of the terminal branches of the internal carotid arteries and the proximal tracts of anterior and middle cerebral arteries. Although surgical revascularization does not significantly change the underlying pathogenic mechanisms, it plays a pivotal role in the management of affected individuals, allowing to decrease the risk of ischemic and hemorrhagic complications. Surgical approaches may be direct (extracranial-intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…In this study, the diameter of the F-STA increased by an average of 23.2% (P < 0.001), the diameter of the MMA increased by an average of 51.0% (P < 0.001), the diameter of the DTA increased by an average of 29.3% (P < 0.001), and the diameter of the distal STA increased by an average of 34.8% (P < 0.001). According to the data above, MMA seems to be the most effective choice for neovascularization induced by indirect revascularization, which is consistent with other studies (17)(18)(19). Although the incidence of perioperative complications was 24.2%, most of them were reversible, and no patient experienced stoke recurrence after the first postoperative month.…”
Section: Advantage Of Sta-mca Anastomosis Combined With Mbh and Dural...supporting
confidence: 91%
“…In this study, the diameter of the F-STA increased by an average of 23.2% (P < 0.001), the diameter of the MMA increased by an average of 51.0% (P < 0.001), the diameter of the DTA increased by an average of 29.3% (P < 0.001), and the diameter of the distal STA increased by an average of 34.8% (P < 0.001). According to the data above, MMA seems to be the most effective choice for neovascularization induced by indirect revascularization, which is consistent with other studies (17)(18)(19). Although the incidence of perioperative complications was 24.2%, most of them were reversible, and no patient experienced stoke recurrence after the first postoperative month.…”
Section: Advantage Of Sta-mca Anastomosis Combined With Mbh and Dural...supporting
confidence: 91%
“…Due to the inadequate caliber of the superficial temporal artery, instead of a combined direct-indirect revascularization, we opted for EDAMPS, which was bilaterally performed with a 3-month interval. Indeed, it has been demonstrated that indirect revascularization improves cerebral hemodynamics and reduces the incidence of subsequent ischemic events in children with moyamoya vasculopathy [8,37,38]. Accordingly, in the present case, we noted regression of the ivy sign on FLAIR images and marked improvement of cerebral blood flow on ASL studies after surgery.…”
Section: Discussionsupporting
confidence: 72%
“…Perioperative complications happen in 9.4-13.6% of BR procedures [116,149,194,205,219,221,226] with a 0-0.5% [188] mortality rate. Indirect BR has a significantly higher postoperative stroke rate than direct techniques [116,205] but fewer haemorrhages and no hyperperfusion syndrome [140,229,230]. The incidence of postoperative surgical complications is higher in Asian than other racial groups (6.51/100,00 inhabitants/year versus 5.21/100,000/persons/year) [198,231].…”
Section: Results Surgical Techniques Of Cerebral Revascularization In Moyamoya Diseasementioning
confidence: 99%